MENINGKATKAN KETERAMPILAN MEMBACA DENGAN MENGGUNAKAN MODEL MULTILITERASI UNTUK SISWA KELAS 4 SEKOLAH DASAR - Dina, Alifia Marsha; Regina, Belinda Dewi; Muzzaki, Abdurrohman (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2025)
Language is one of the tools of knowledge. The highest competency that is mastered in forming language skills is the ability to read. However, in reality at Ampeldento 01 Karangploso Elementary School it is still found that students' reading comprehension skills are very low, especially in grade 4 students. The purpose of this study was to improve the reading comprehension skills of 4th grade students of SDN Ampeldento 01 Karangploso by applying the multiliteracy model of reading comprehension through picture stories. The research method used was Classroom Action Research (PTK). The research model used is the John Elliot model which is carried out in 2 stages. The data collection techniques used were observation, interview, and questionnaire distribution through the evaluation test results of 28 students. The results obtained showed an increase in the teacher's ability to improve students' abilities by using the multiliteracy model. The results of the study concluded a significant increase with very good quality in Indonesian learning outcomes with main idea material. This can be proven from the average results of students where in cycle 1 shows that the average value of students only reaches 61.5 so that it is still categorized as sufficient, with a percentage of student completeness of 39% this condition indicates that the learning strategy in the first cycle is not fully effective and still needs guidance in improving student learning outcomes. Whereas in cycle 2 the average score of students only reached 85 so that it could be categorized as very good, with a percentage of student completeness of 89%, this condition indicates that the learning strategy in the second cycle was very good and could improve students' understanding when looking for main ideas in reading. In addition, it can also improve students' reading skills, especially at grade 4 elementary school level.